GUILLAIN-BARRÉ SYNDROME (GBS): 'AMAN' VARIETY CASE STUDY IN TABASCO, MEXICO - Morales Peralta, Alejandra; Pérez Rosado, Víctor Manuel; Morales Jiménez, Daniela Alexandra (Kuxulkab', 2022)
Guillain-Barré syndrome is a rare condition characterized by an attack of the patient's immune system towards the peripheral nerves. Due to its low incidence, the study of a case in the state of Tabasco is important, where it was analyzed from diagnosis to treatment.
Keywords: Guillain-Barré syndrome; Diagnosis; Treatment